Analysis of over-consumption of natural resources and the ecological trade deficit in China based on ecological footprints. (February 2016) - Gao, Jixi; Tian, Meirong
Highlights: Developed a resource excessive consumption index to assess ecological pressure. Evaluated impact of international trade on ecological footprint and biocapacity. Provided specific suggestions on promoting new policies, technologies, etc. The method and indices can be applied in the regional scale. Abstract: China has experienced unprecedented economic development in recent years and is now facing severe challenges caused by the over-consumption of resources and by ecological and environmental degradation. To assess the influence of resource exploitation and ecological trade, we have developed an index of excessive resource consumption based on the concepts of ecological deficit and ecological over-shoot, and we have used the ecological trade deficit to assess the pressure created by the export and import of resources and products. Our analysis indicated that China's consumption footprint surpassed its biocapacity in 1983, leading to an ecological deficit, and the production footprint surpassed its biocapacity in 1986, leading to an ecological over-shoot, as the over-consumption of natural resources grew. By 2010, 3.6 times the current area of bioproductive land was needed to provide sufficient resources to meet the consumption. China has been encouraging the development of exporting enterprises by implementing a series of financial and tax incentives, which have stimulated the economy in the short-term but have gradually increased the ecological trade deficit since 2000.